2001
DOI: 10.1002/ffj.1054
|View full text |Cite
|
Sign up to set email alerts
|

Human gustation and flavour

Abstract: Taste is an essential component of flavour. Although taste carries fewer distinctive qualities than odour, it provides an essential base on which aroma builds to generate the widely varying flavour of our foods and beverages. The present review covers a wide range of perceptual/psychophysical topics on taste. The first section reviews the taste research questions of early last century; the second section addresses the psychophysical taste research topics of the last few decades; and in the third section, the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 152 publications
2
23
2
1
Order By: Relevance
“…Compared to the ICA trial, this 11-year old participant with CA was able to correctly identify the umami stimulus at the second highest concentration of 5 × 10 -3 M. This is a new finding, which was not established in any of the previous studies looking at taste function in patients with CA. Compared to the reported normal population threshold for MSG at 5 × 10 -4 M, the participant did require a higher stimulant concentration for correct identification [5].…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Compared to the ICA trial, this 11-year old participant with CA was able to correctly identify the umami stimulus at the second highest concentration of 5 × 10 -3 M. This is a new finding, which was not established in any of the previous studies looking at taste function in patients with CA. Compared to the reported normal population threshold for MSG at 5 × 10 -4 M, the participant did require a higher stimulant concentration for correct identification [5].…”
Section: Discussioncontrasting
confidence: 62%
“…In this trial, sour was correctly identified at the second highest concentration of 1.6 × 10 -4 M. This threshold is higher than the threshold findings by Salles et al of 7.8 x10 -5 M and the normal taste threshold of 7 × 10 -5 M [2,5]. While sour was one of the tastes correctly identified in the trial by McMicken et al, a direct comparison regarding concentration threshold cannot be made as a different stimulus, acetic acid, was used.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…For points of comparison, research shows that normal populations detected taste stimuli on average at 0.22 g/L sucrose (sweet), 0.06 g/L sodium chloride (salty), 0.007 g/L acetic acid (sour), 0.097 g/L caffeine (bitter), and 0.085 g/L monosodium glutamate (umami) [3]. One male congenital aglossia subject was found to be able to discern concentrations of solutions of sweet, salty, sour, and bitter brushed on the small palate of 3% (30 g/L) cane sugar, 1% (10 g/L) sodium chloride, 0.1% (1 g/L) sulfuric acid, and 0.01% quinine (0.1 g/L), respectively [4].…”
Section: Introductionmentioning
confidence: 99%